Non-verbal IQ and change in restricted and repetitive behavior throughout childhood in autism: a longitudinal study using the Autism Diagnostic Interview-Revised - Courchesne, V.; Bedford, R.; Pickles, A.; Duku, E.; Kerns, C.; Mirenda, P.; Bennett, T.; Georgiades, S.; Smith, I. M.; Ungar, W. J.; Vaillancourt, T.; Zaidman-Zait, A.; et al. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Restricted and repetitive behavior (RRB) is one of the characteristic features of Autism Spectrum Disorder. This domain of symptoms includes a broad range of behaviors. There is a need to study each behavior individually to better understand the role of each in the development of autistic children. Moreover, there are currently no longitudinal studies investigating change in these behaviors over development. Methods The goal of the present study was to explore the association between age and non-verbal IQ (NVIQ) on 15 RRB symptoms included in the Autism Diagnostic Interview-Revised (ADI-R) over time. A total of 205 children with ASD were assessed using the ADI-R at time of diagnosis, at age 6 years, and at age 11 years, and with the Wechsler Intelligence Scales for Children—Fourth Edition (WISC-IV) at age 8 years. Results The proportion of children showing each RRB tended to diminish with increasing age, except for sensitivity to noise and circumscribed interests, where the proportion increased over time. Although there was no significant main effect of NVIQ, there was a significant interaction between age and NVIQ. This was mainly driven by Difficulties with change in routine, for which higher NVIQ was associated with the behavior remaining relatively stable with age, while lower NVIQ was associated with the behavior becoming more prevalent with age. Limitations The study focused on the presence/absence of each RRB but did not account for potential changes in frequency or severity of the behaviors over development. Furthermore, some limitations are inherent to the measures used. The ADI-R relies on parent report and hence has some level of subjectivity, while the Wechsler intelligence scales can underestimate the intellectual abilities of some autistic children. Conclusions These results confirm that specific RRB are differentially linked to age and NVIQ. Studying RRB individually is a promising approach to better understanding how RRB change over the development of autistic children and are linked to other developmental domains.